2012
DOI: 10.1136/tobaccocontrol-2012-050465
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of internet and telephone treatment for smoking cessation: an economic evaluation of The iQUITT Study

Abstract: Background Internet and telephone treatments for smoking cessation can reach large numbers of smokers. There is little research on their costs and the impact of adherence on costs and effects. Objective To conduct an economic evaluation of The iQUITT Study, a randomised trial comparing Basic Internet, Enhanced Internet and Enhanced Internet plus telephone counselling (‘Phone’) at 3, 6, 12 and 18 months. Methods We used a payer perspective to evaluate the average and incremental cost per quitter of the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 39 publications
0
66
0
Order By: Relevance
“…However, we did not attempt to carry out an economic evaluation of TFU for colorectal cancer. Other studies have demonstrated cost savings when using telephone contact with NHS patients instead of face to face consultations (Donohue et al, 2014, Gordon et al, 2014, Graham et al, 2013, Pinnock et al, 2005, Uppal et al, 2004. Further research is needed with a larger main trial to examine the economic costs of TFU for colorectal cancer to patients and the NHS in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not attempt to carry out an economic evaluation of TFU for colorectal cancer. Other studies have demonstrated cost savings when using telephone contact with NHS patients instead of face to face consultations (Donohue et al, 2014, Gordon et al, 2014, Graham et al, 2013, Pinnock et al, 2005, Uppal et al, 2004. Further research is needed with a larger main trial to examine the economic costs of TFU for colorectal cancer to patients and the NHS in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Use is not restricted by geographical location and costs are often minimal or nonexistent to users through coverage by employers, health plans, or states, making it an ideal resource for those who do not have easy access to other cessation services. The costs of Internet programs are relatively fixed, resulting in greater efficiency as use increases (6, 13). Several large-scale randomized trials have shown quit rates of 18–20% at 12 months (14, 15) and meta-analyses and systematic reviews support the effectiveness of tailored and interactive interventions (5, 7, 8, 16).…”
mentioning
confidence: 99%
“…We used a framework approach to interpretation of the data 111 as we felt that it best suited the practical and applied nature of the research to answer questions about health service development. Although this approach is based in the original accounts and observations of the participants, and therefore 'grounded' and inductive, it uses a priori categories to analyse the data.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, reporting costs using the number of participants in a clinical trial will not provide an accurate reflection of the true cost per patient if the trial were rolled out to a wider patient group. 111 It is therefore recommended that the likely take-up rate for the intervention is taken into account to allow a more accurate estimate of the average costs per patient associated with ongoing costs for maintaining internet-based elements. 18 We therefore adjusted the ongoing costs associated with the web tool to give a more accurate estimate of these if the trial were rolled out.…”
Section: Resource Use and Cost Definitionmentioning
confidence: 99%
See 1 more Smart Citation